TGF-ß1 signalling, connecting aberrant inflammation and colorectal tumorigenesis - Paterson, I.C.; Skeen, V.R.; Paraskeva, C.; Williams, A.C. (Bentham Science Publishers, 2012)
TGF-ß1 is an anti-inflammatory cytokine recognised as a key regulator of immunological homeostasis and inflammatory responses. Furthermore, TGF-ß1 is important for the regulation of cell growth, differentiation and apoptosis in a wide range of tissues including the intestinal epithelium. Reduced TGF-ß1 activity is thought to be responsible for the development of autoimmune disorders in several pathological conditions, including inflammatory bowel disease [IBD]. Although the cause of IBD is not yet known, research has shown that a number of factors may be involved including environment, diet and genetics, as well as cytokine exposure. Importantly, IBD is also associated with an increased lifetime risk of developing colorectal cancer, which remains the fourth most common cancer worldwide, representing a significant therapeutic challenge. As functionally implicated in both maintenance of the immune response and tissue homeostasis in the colon, TGF-ß1 signalling potentially sits at the crossroads between aberrant inflammation and colorectal tumorigenesis. Hence, the purpose of this paper is to review the evidence for cross talk between TGF-ß1 signalling and pathways important for colorectal tissue homeostasis, with the emphasis on understanding how deregulation of TGF-ß1 signalling contributes not only to aberrant inflammatory disease but also to colorectal tumour progression.